(untitled) (Rasividya : Jurnal Pendidikan, 2025)
This class action research aimed to ascertain if the implementation of a mastery learning paradigm utilizing pictorial media may enhance students’ academic performance. This investigation employed two iterations of action research. Each circle comprises four stages: preparation, action, observation, and reflection. The employed data gathering approach was the assessment of learning outcomes. The employed data analysis technique was descriptive analysis. The study results indicated that students’ learning achievement improved from the original data to cycle II, with the starting average accomplishment recorded at 70.45, increasing to 75.68 in cycle I, and further rising to 79.09 in cycle II. The initial learning completeness of 50% in Cycle I improved to 72.73%, and in Cycle II, it reached 95.45%. The Mastery Learning paradigm, including graphic media used by educators, has effectively enhanced student learning results and can provide as an alternate technique for Hinduism education